2016
DOI: 10.1017/s0029665116000197
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin status, MTHFR genotype and blood pressure: current evidence and implications for personalised nutrition

Abstract: Clinical deficiency of the B-vitamin riboflavin (vitamin B 2 ) is largely confined to developing countries; however accumulating evidence indicates that suboptimal riboflavin status is a widespread problem across the developed world. Few international data are available on riboflavin status as measured by the functional biomarker, erythrocyte glutathione reductase activation coefficient, considered to be the gold standard index. One important role of riboflavin in the form of flavin dinucleotide is as a co-fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 104 publications
(131 reference statements)
1
18
0
Order By: Relevance
“…Of the six independently associated nutrient intakes, alcohol, tryptophan and riboflavin elicited large effects, in line with previously reported literature [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Of the six independently associated nutrient intakes, alcohol, tryptophan and riboflavin elicited large effects, in line with previously reported literature [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…RIBOFLAVIN: Riboflavin, also known as vitamin B₂, is a water-soluble vitamin found in food, predominantly milk and egg products [ 41 ], and also used as a dietary supplement. The effect of riboflavin in reducing BP has been previously reported [ 32 ]. Riboflavin acts on BP in a gene-nutrient interaction involving the gene encoding methylenetetrahydrofolate reductase [ 33 ], potentially stabilising variants within this gene to restore 5-methyltetrahydrofolate concentrations to improve nitric oxide bioavailability, a potent vasodilator in BP control [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency in these vitamins has been shown to result in tinnitus [ 24 ], and supplementation may improve the symptom. Moreover, vitamin B 2 performs its role as a cofactor for metabolism of other B vitamins [ 25 ]. Our large cohort study indicates that vitamin B 2 and B 3 may have critical roles in prevention of tinnitus, perhaps by assisting to maintain functions of the vitamin B complex.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals carrying the 5,10-methylenetetrahydrofolate reductase ( MTHFR ) 677TT polymorphism, which is reported to be found in some populations, have a ≤32% higher risk of CVD and hypertension. A number of recent randomized controlled trials (RCTs) showed that riboflavin supplementation can significantly reduce systolic blood pressure by 5–13 mm Hg in these genetically at-risk adults ( 55 ).…”
Section: Discussionmentioning
confidence: 99%